AquaNet - 18S Eukaryotes Reads from Erken AquaNet platform, 2017-06-13–2017-09-11 - Erken Laboratory (Uppsala University, 2019)
Mesocosm experiment focusing on fish pulse and light reduction as treatment effects ran simultaneously at the SITES stations Asa, Erken, Skogaryd, Svartberget and Bolmen during summer 2017. Data contains number of reads per Operational Taxonomic Unit of 18S Eukaryotes.
Erken Laboratory (2019). AquaNet - 18S Eukaryotes Reads from Erken AquaNet platform, 2017-06-13–2017-09-11 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/G0xGCOyuYaWBlApsgw60_rTi
Keywords: SITES AquaNet; Ecosystem functions; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap